The effect of using health behavior modification model on health literacy health behavior and fasting blood sugar level in type 2 Diabetic patients with uncontrolled glycemic Nong Muang District Lopburi Province - Chamchan, Dissapol; Chusak, Thassaporn; Banchonhattakit, Pannee; Wongsakoonkan, Watcharaporn (Journal of Medical and Public Health Region 4, 2026)
Type 2 Diabetic patients with uncontrolled glycemic significantly increases the risk of complications and mortality. Traditional behavior modification programs often focus solely on diet, exercise, and stress management, lacking comprehensive health care and patient monitoring. This gap leads to reduced patient awareness and engagement, resulting in suboptimal glycemic control.​Objective: To develop and assess a comprehensive health behavior modification model aimed at improving glycemic control among type 2 Diabetic patients with uncontrolled glycemic in Lopburi Province, Thailand.​Methods: A randomized controlled trial (RCT) with pretest-posttest design was conducted. Sixty participants were randomly assigned to either the experimental group (n = 30) or the control group (n = 30). The experimental group received a multifaceted intervention comprising:​Health Education: Information on diabetes management, including diet, exercise, stress reduction, and self-monitoring. ​Behavioral Support: Regular follow-ups and motivational support to encourage adherence to self-care practices.​ Community Engagement: Involvement in group activities to enhance social support and reinforce behavior changes.​The control group received standard care without additional interventions. Data were collected at baseline and after the intervention using questionnaires assessing health literacy, self-care behaviors, and fasting blood glucose (FBG) levels. Paired t-tests compared pre- and post-intervention changes within groups, while independent t-tests assessed differences between groups.​Results: Post-intervention, the experimental group demonstrated significant improvements:​Health Literacy: Increased average scores, with a statistically significant difference (p<0.05).​Self-Care Behaviors: Enhanced adherence to recommended health practices, showing a significant difference (p<0.05).​Glycemic Control: Mean FBG levels decreased notably, with a significant difference (p<0.05).​Comparing between groups, the experimental group exhibited higher health literacy and self-care behavior scores, and lower FBG levels than the control group, all with significant differences (p<0.05).​Conclusion: Implementing a comprehensive health behavior modification model effectively enhances health literacy, self-care behaviors, and glycemic control among T2DM patients. It is recommended that healthcare providers adopt this approach, incorporating continuous support and monitoring to sustain behavior changes and improve disease management.